KINETIC STUDIES OF THE ADSORPTION OF MANGANESE (II) AND NICKEL (II) IONS ONTO MODIFIED OIL PALM MESOCARP FIBER - M, MUSAH; J. T, MATHEW; Y, AZEH; U. M, BADEGGI; Z, ABDULHAMID; A. I, MUHAMMAD (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The removal of Mn2+ and Ni2+ from aqueous solutions onto chemically modified oil palm mesocarp fiber using the batch adsorption method at 30, 60, 90, 120 and 150 minutes were studied. The influence of contact time was used to determine experimental, qe(exp) and theoretical, qe(cal) values. Three adsorption kinetic models: pseudo first-order, pseudo second-order and elovich models were tested. The correlation coefficient (R2) values for first order kinetics were 0.4630 and 0.1020 for Mn2+ and Ni2+ respectively. R2 values obtained for pseudo second kinetics of Mn2+ and Ni2+ adsorption were 0.9950 and 0.9970 respectively and were higher than 0.9710 and 0.9260 obtained for elovich model. Large difference existed between the qe(exp) and qe(cal) values (0.1632 and 0.0033) of pseudo first order and low difference was obtained for pseudo second order (0.1653 and 0.1676) for the adsorption of Ni2+. Similar trend was observed for the adsorption of Mn2+. The sum of square of error calculated to compare the fitness of the adsorption kinetics indicated that the adsorption of Mn2+ and Ni2+ followed a pseudo second-order kinetics.